2017
DOI: 10.1590/1806-9282.63.01.57
|View full text |Cite
|
Sign up to set email alerts
|

Decompensated chagasic heart failure versus non-chagasic heart failure at a tertiary care hospital: Clinical characteristics and outcomes

Abstract: DecompensateD chagasic heart failure versus non-chagasic heart failure at a tertiary care hospital: clinical characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
1
7
1
5
Order By: Relevance
“…In the setting of decompensated heart failure, a recent study compared the prognosis of patients with Chagas cardiomyopathy to that of patients with other etiologies; no difference was found regarding in-hospital mortality, but Chagas patients had a higher rate of hospital readmission. [ 25 ] Additionally, our center is a tertiary hospital dedicated to cardiology that treats patients with advanced heart failure, with a higher expected mortality compared with that in community hospitals. In this sense, it is remarkable that a third of our patients received inotropes during their hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of decompensated heart failure, a recent study compared the prognosis of patients with Chagas cardiomyopathy to that of patients with other etiologies; no difference was found regarding in-hospital mortality, but Chagas patients had a higher rate of hospital readmission. [ 25 ] Additionally, our center is a tertiary hospital dedicated to cardiology that treats patients with advanced heart failure, with a higher expected mortality compared with that in community hospitals. In this sense, it is remarkable that a third of our patients received inotropes during their hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported the presence of lower limb edema in 94.6% and of jugular engorgement of 48.6% in 37 Chagas patients as compared to 85.9% and 37.4%, respectively, in 99 patients with other etiologies; the differences were not statistically significant, what might be partially explained by the relatively small number of patients. [ 25 ] The finding of right ventricular dysfunction has been consistently described among patients with Chagas cardiomyopathy with and without heart failure. [ 28 , 29 , 30 ] Previous authors have described that pulmonary congestion is a rare phenomenon among Chagas patients and with a mild presentation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Although several prior studies have compared individuals with Chagasic HFrEF to others with ischemic or nonischemic cardiomyopathy (but not both concomitantly), these have been mainly single-center reports of often highly selected cohorts (eg, transplant referrals) usually markedly undertreated by contemporary standards. [12][13][14][15][16][17][18][19][20]28 These prior reports included between 25 and 246 patients with Chagas' cardiomyopathy and 50 to 454 patients in the comparator group, usually did not report detailed characterization of participants (eg, in relation to prior history and biomarkers) and often did not adjust for differences in a multivariable analysis when comparing outcomes across etiologic groups. [13][14][15][16][17][18][19][20][21]28 Despite these differences, it is possible to make some comparisons with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20]28 These prior reports included between 25 and 246 patients with Chagas' cardiomyopathy and 50 to 454 patients in the comparator group, usually did not report detailed characterization of participants (eg, in relation to prior history and biomarkers) and often did not adjust for differences in a multivariable analysis when comparing outcomes across etiologic groups. [13][14][15][16][17][18][19][20][21]28 Despite these differences, it is possible to make some comparisons with our findings. In both the prior studies and in ours, Chagasic patients were notable by their younger age and lower preponderance of males (especially when compared with patients with ischemic HFrEF).…”
Section: Discussionmentioning
confidence: 99%
“…Corroborando outros estudos, nossa população apresenta renda individual baixa, de 1 a 2 salários mínimos(LINHARES et al, 2016;DO NASCIMENTO et al, 2016;FERNANDES et et., 2016;DE ALMEIDA NETO et al, 2016;.Estudo desenvolvido em hospitais privados e públicos observou que pacientes com seguimento em instituições particulares se mantinham por maior tempo em tratamento e possuíam uma evolução positiva da IC quando comparados a indivíduos de baixa renda. Estes últimos apresentaram maior porcentagem de abandono do tratamento medicamentoso, de falta às consultas anuais e frequente descompensação da cardiopatia(TAVARES, 2004) A classe econômica, assim como o nível de instrução, refletem-se no cenário saúdedoença e, apesar de serem medidas relativas à desigualdade em distribuição de renda e acesso a educação, estão diretamente associadas a pior resposta às ações preventivas ,com aumento das hospitalizações, desenvolvimento de comorbidades e elevação da taxa de mortalidade, tornando-se um problema de ordem global (MARGOTO; COLOMBO;GALLANI, 2009;GUTIERREZ;MARQUES, 2012;DO NASCIMENTO et al, 2016;.A maior prevalência do sexo feminino em nossa população, muito embora pequena em relação ao número de homens, contradiz a literatura nacional e internacional, na qual há presença do sexo masculino é maior na IC (SACCOMANN; CINTRA;GALLANI, 2011; MUSSI et al, 2013;SANTOS et al, 2017;VELLONE et al, 2017;NORDGREN;SÖDERLUND, 2017;EVANGELISTA et al, 2017).As DCV representam 50% das causas de morte em mulheres, estando diretamente relacionadas com a idade. Em mulheres o desenvolvimento de cardiopatias ocorre dez a quinze anos mais tarde em comparação com os homens, sendo que o risco aumenta nas mulheres após a menopausa (CHAGAS; DOURADO, P.;DOURADO, L., 2014;AHMETI et al, 2017.…”
unclassified